2014
DOI: 10.1103/physrevb.90.045128
|View full text |Cite
|
Sign up to set email alerts
|

Orbital polarization in strainedLaNiO3: Structural distortions and correlation effects

Abstract: Transition-metal heterostructures offer the fascinating possibility of controlling orbital degrees of freedom via strain. Here, we investigate theoretically the degree of orbital polarization that can be induced by epitaxial strain in LaNiO3 films. Using combined electronic structure and dynamical mean-field theory methods we take into account both structural distortions and electron correlations and discuss their relative influence. We confirm that Hund's rule coupling tends to decrease the polarization and p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
47
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 63 publications
(111 reference statements)
7
47
1
Order By: Relevance
“…II, the structure becomes monoclinic (C2/c) under the epitaxial constraint, which changes the pattern of octahedral rotations. The NiO 6 θ xy and θ z , which lie in and out of the plane of applied strain, respectively. In addition, there are also two distinct Ni-O bond lengths, r xy and r z lying in (out of) the strain plane.…”
Section: B Strained Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…II, the structure becomes monoclinic (C2/c) under the epitaxial constraint, which changes the pattern of octahedral rotations. The NiO 6 θ xy and θ z , which lie in and out of the plane of applied strain, respectively. In addition, there are also two distinct Ni-O bond lengths, r xy and r z lying in (out of) the strain plane.…”
Section: B Strained Filmsmentioning
confidence: 99%
“…LaNiO 3 is an appropriate test case for this study because it has strong electronic correlations, yet remains a Fermi liquid down to low temperatures. In addition, there has been a great deal of interest in potential exotic physics in LaNiO 3 , including engineering orbital polarization with epitaxial strain [5][6][7] and a cupratelike Fermi surface via heterostructuring [8], and precise knowledge of the predictive capabilities of theory will aid in engineering new emergent properties in the nickelates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MIT in RNiO 3 has drawn increasing attention recently, not only due to their fundamental electronic structure like electrons interaction between nickel 3d and oxygen 2p bands, but also driven by the promise to emulate cuprate superconductors. [1][2][3][4] The electronic behavior of RNiO 3 has been explained by many researchers under Mott-Hubbard type 5,6 or charge-transfer type materials. 1 The room-temperature metallic state in RNiO 3 arises due to the overlapping of O-2p…”
mentioning
confidence: 99%
“…[3][4][5] In particular, by selecting the film/substrate lattice misfit, one can tune the B-O bond lengths and the B-O-B bond angles (Θ), modifying the crystal field and bandwidth of perovskite compounds. 6,7 The effect of epitaxial strain (ε xx ), induced by the film/substrate lattice parameter mismatch, has been extensively investigated in the past. 2,5,8 Both theoretical and experimental studies have suggested that, beyond pure strain effects, substrate symmetry and orientation, which can modify the distortions and tilting of the oxygen octahedra network, play an important role and are key to understanding the complex properties of oxide heterostructures.…”
mentioning
confidence: 99%